STUDI KOMPARASI PRINSIP-PRINSIP KEUANGAN ISLAM DENGAN SUSTAINABLE FINANCE DALAM ISLAM - Habibah Zulaiha; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2025)
Sustainable finance and Islamic finance have significant potential to facilitate sustainable development. Both systems are continuously developed, researched, and developed by scholars, global industry players, and policy makers. However, to the best of the author's knowledge, only a few studies have specifically explored the principles of Islamic finance and sustainable finance. Therefore, this study aims to examine and highlight the principles of both concepts along with the development of a better financial model based on ethical values. Using a qualitative approach and based on comparative research, this study concludes that sustainable and inclusive development is the main point of both concepts. Islamic finance itself promises a more sustainable model for the financial industry.